Evaluation of nicotine patch adherence measurement using self-report and saliva cotinine among abstainers in a smoking cessation trial. (1st May 2020) - Schnoll, Robert; Paul Wileyto, E.; Gross, Robert; Hitsman, Brian; Hawk, Larry W.; Cinciripini, Paul; George, Tony P.; Benowitz, Neal L.; Fen Lubitz, Su; Ashare, Rebecca; Tyndale, Rachel F.; Lerman, Caryn
Highlights: Self-reported patch use and saliva cotinine were modestly correlated. Self-reported 7-day and 3-week patch use is correlated with saliva cotinine after one week of treatment. The optimal cotinine cut-point for adherence may vary by nicotine metabolism rate. Abstract: Background: Adherence to nicotine patches relates to cessation. This is the first study to examine the validity of self-reported nicotine patch adherence relative to saliva cotinine. Methods: We used data from 198 clinical trial participants who received 11 weeks of nicotine patches, self-reported patch use, had saliva cotinine 1-week after the start of treatment assessed, and were not smoking when saliva was collected (CO < 6). Self-reported patch adherence was defined as: 3-day (before saliva collection), 7-day (before saliva collection), 3-week use (7 days before, and 14 days after, saliva collection), and 11-week use (7 days before, and 10 weeks after, saliva collection). Analyses, including receiver operating characteristic curves, considered differences in nicotine metabolism. Sensitivity, specificity and positive (PPV) and negative predictive value (NPV) assessed optimal cotinine cut-point for adherence. Results: Self-reported 7-day (r = 0.13) and 3-week (r = 0.13) patch use marginally correlated with week 1 cotinine (p's = 0.08) but not 3-day or 11-week. Significant area under the curve (AUC) values of 0.67 (95 %CI: 0.55−0.79) and 0.72 (95 %CI: 0.57−0.88) were found using 7-day self-report for the overall sample and for slow metabolizers (p's<0.01), but not for normal metabolizers. Optimal 1-week cotinine cut-points using 7-day self-report were 170 ng/mL (overall) and 184 ng/mL (slow), with sensitivity = 0.56−0.62, specificity = 0.69−0.78, PPV = 0.96−0.97, and NPV = 0.13−0.14. Conclusions: Among CO-confirmed abstainers, self-reported patch use and saliva cotinine assessed 1-week into treatment, were modestly correlated and optimal cotinine cut-point differed by rate of nicotine metabolism. Seven-day patch use may be a more valid self-report measure of patch adherence based on cotinine than 3-day, 3-week, or 11-week. Rate of nicotine metabolism may affect this relationship.